UNDERSTANDING CONSUMER SWITCHING INTENTIONS TOWARD TELKOMSEL ONE IN WEST JAVA : A PUSH-PULL-MOORING MODEL APPROACH - Juan Ramadheni Hermawan; Nila Armelia Windasari; Husnita Husnita (LPPM STIE Muhammadiah Bandung, 2025)
In the Society 5.0 era, seamless digital connectivity is essential. Telkom, through its “Five Bold Moves” transformation agenda, integrated IndiHome into its mobile subsidiary, Telkomsel, to streamline operations and enhance customer experience. Following this, Telkomsel launched Telkomsel One, a Fixed Mobile Convergence (FMC) product that combines mobile and fixed broadband into a single platform. The service offers a bundled package of internet, voice, and entertainment for a unified experience at home and on the go. Despite its strategic potential, adoption has not yet reached its potential in West Java, highlighting the need to understand consumer behavior better. This study applies the Push – Pull – Mooring (PPM) model to examine switching intentions toward Telkomsel One. Push factors include dissatisfaction, pull factors reflect perceived benefits and convenience, and mooring factors involve loyalty and switching costs. The study also explores generational differences among Generation Z, Millennials, and Generation X. Using SEM-PLS with 300 respondents in West Java, findings show that pull factors have the strongest influence on switching intentions, followed by moderate push effects, while mooring factors act as a significant barrier, particularly for older users. Gen Z is digitally open and engaged, but they are not typically the main decision-makers when it comes to household connectivity products. Millennials show a strong intent to adopt customizable services that offer clear value and fairness. Gen X is the most resistant due to attachment and complexity, requiring trust-driven and personalized support.